Design and assembly of high temperature distributed aero-engine control system demonstrator - Riches, S; Warn, C; Cannon, K; Rickard, G; Stoica, L; Johnston, C (IMAPS-International Microelectronics and Packaging Society, 2014)
This paper covers the development of a distributed high temperature electronics demonstrator for integration with sensor elements to provide digital outputs that can be used by the FADEC (Full Authority Digital Electronic Control) system or the EHMS (Engine Health Monitoring System) on an aircraft engine. This distributed electronics demonstrator eliminates the need for the FADEC or EHMS to process the sensor signal, which will assist in making the overall system more accurate and efficient in processing only digital signals. This will offer weight savings in cables, harnesses and connector pin reduction. The design concept was to take the output from several on-engine sensors, cany out the signal conditioning, multiplexing, analogue to digital conversion and data transmission through a serial data bus. The unit has to meet the environmental requirements of DO-160 with the need to operate at 200°C, with short term operation at temperatures up to 250°C. The work undertaken has been to design an ASIC based on 1.0μm Silicon on Insulator (SOI) device technology incorporating sensor signal conditioning electronics for sensors including resistance temperature probes, strain gauges, thermocouples, torque and frequency inputs. The ASIC contains analogue multiplexers, temperature stable voltage band-gap reference and bias circuits, ADC, BIST, core logic, DIN inputs and two parallel ARINC 429 serial databuses. The ASIC was tested and showed to be functional up to a maximum temperature of 275° C. The ASIC has been integr ated with other high temperature components including voltage regulators, a crystal oscillator, precision resistors, silicon capacitors within a hermetic hybrid package. The hybrid circuit has been assembled within a stainless steel enclosure with high temperature connectors. The high temperature electronics demonstrator has been shown to operate from -4(fC to +250°C. This work has been carried out under the EU Clean Sky HIGHTECSproject with the Project being led by Turbomeca (Fr) and carried out by GE Aviation Systems (UK), GE Research -Munich (D) and Oxford University (UK).